Podłużne badanie zdolności językowych jako konceptu dynamicznego - Biedroń, Adriana (Neofilolog, 2019)
In contemporary literature foreign language ability is considered a dynamic concept, that is, subject to an evolutionary development in interaction with the environment and potentially trainable (Sternberg, 2002). Sternberg’s Triarchic Theory of Human Intelligence is based on an assumption that abilities are forms of developing expertise. An important educational implication of this statement is that abilities are flexible and pliable rather than fixed and that they can be taught. The purpose of the paper is to present results from the first stage of a longitudinal study of foreign language aptitude on a sample of English philology students. The goal of this study, conducted in cooperation with a psychologist, is to analyze the students’ cognitive abilities and establish whether they are subject to a dynamic change.